The Effect of NPK Fertilizer and Chicken Manure Fermented on Growth and Yield of Cucumis melo L. (Alisha Variety) - Al Adawiah, Alin Robiah; Priyadi, Rudi; Billyan, Billyan; Adawiah, Alin Robiah Al; Dina, Aslikh Lana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Melon is a horticultural crop that has high-income potential, but in 2023 the production of melon in Indonesia declines drastically. Hence, research and collaboration to increase the production of melon in Indonesia is essential. This study was aimed to analyze the effect of NPK fertilizer and chicken manure fermented on growth and yield of melon (Alisha variety). This study conducts by analysing the effect of combination of NPK fertilizer and chicken manure fermented on growth and yield Cucumis melo L. alisha variety using Randomized Group Design (RGD) consisting of 7 treatment combinations. The parameters of plant height, number of leaves, stem diameter, fruit weight, and the level of sweetness (oBrix) of melon fruit were analyzed using Duncan’s Multiple Range Test (DMRT) at P<0.05. The results show that 300 kg/ha NPK fertilizer + 0 t/ha chicken manure fermented gave the best growth and yield with a melon weight of 61.50 t/ha, however, it was not significantly different from the combination treatment of 100 kg/ha NPK fertilizer + 15 t/ha chicken manure (F) on fruit weight per plot. The results of this study will be the basis of considerations in using a combination of NPK and chicken manure fermented to increase the growth and yield of Cucumis melo L. (Alisha variety).